PENGARUH KOMITMEN ORGANISASI DAN DAN ORGANIZATIONAL CITIZHENSHIP BEHAVIOR (OCB) TERHADAP KINERJA KARYAWAN - Amsya, Akmal Huda Maulana; Alim, Syahirul (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study a$ims to exa$min$e the in$fluen$ce of orga$n$iza$tion$a$l commitmen$t a$n$d Orga$n$iza$tion$a$l Citizen$ship Beha$vior (OCB) on$ employee performa$n$ce a$t PT Griya$ Sewu Berka$h Pertiwi, Ma$la$n$g City. The ba$ckgroun$d of this resea$rch is ba$sed on$ the importa$n$ce of huma$n$ resources who possess high commitmen$t a$n$d positive orga$n$iza$tion$a$l beha$vior in$ order to improve the effectiven$ess a$n$d productivity of compa$n$ies, especia$lly in$ the in$crea$sin$gly competitive property in$dustry. This resea$rch uses a$ qua$n$tita$tive method with a$n$ a$ssocia$tive a$pproa$ch. Da$ta$ were collected through question$n$a$ires distributed to 40 respon$den$ts who a$re a$ctive employees of the compa$n$y. The da$ta$ a$n$a$lysis techn$ique employed is multiple lin$ea$r regression$. The results show tha$t simulta$n$eously, orga$n$iza$tion$a$l commitmen$t a$n$d OCB ha$ve a$ sign$ifica$n$t effect on$ employee performa$n$ce. Pa$rtia$lly, both orga$n$iza$tion$a$l commitmen$t a$n$d OCB a$lso ha$ve a$ positive a$n$d sign$ifica$n$t impa$ct on$ performa$n$ce. These fin$din$gs rein$force tha$t the higher the level of orga$n$iza$tion$a$l commitmen$t a$n$d OCB, the better the employee performa$n$ce. This resea$rch is expected to provide pra$ctica$l con$tribution$s for compa$n$y ma$n$a$gemen$t in$ efforts to improve employee performa$n$ce by stren$gthen$in$g commitmen$t a$n$d fosterin$g a$ positive work culture.